The Contribution of Proprioceptive Information to Postural Control in Elderly and Patients with Parkinson’s Disease with a History of Falls - Bekkers, Esther M. J.; Dockx, Kim; Heremans, Elke; Vercruysse, Sarah; Verschueren, Sabine M. P.; Mirelman, Anat; Nieuwboer, Alice (Frontiers in Human Neuroscience, 2014)
Proprioceptive deficits negatively affect postural control but their precise contribution to postural instability in Parkinson’s disease (PD) is unclear. We investigated if proprioceptive manipulations differentially affect balance, measured by force plates, during quiet standing in 13 PD patients and 13 age-matched controls with a history of falls. Perceived limits of stability (LoS) were derived from the differences between maximal center of pressure (CoP) displacement in anterior-posterior (AP) and medio-lateral (ML) direction during a maximal leaning task. Task conditions comprised standing with eyes open (EO) and eyes closed (EC), (1) on a stable surface; (2) an unstable surface and (3) with Achilles tendon vibration. CoP displacements were calculated as a percentage of their respective LoS. Perceived LoS did not differ between groups. PD patients showed greater ML CoP displacement than elderly fallers (EF) across all conditions (p = 0.043) and tended to have higher postural sway in relation to the LoS (p = 0.050). Both groups performed worse on an unstable surface and during tendon vibration compared to standing on a stable surface with EO and even more so with EC. Both PD and EF had more AP sway in all conditions with EC compared to EO (p < 0.001) and showed increased CoP displacements when relying on proprioception only compared to standing with normal sensory input. This implies a similar role of the proprioceptive system in postural control in fallers with and without PD. PD fallers showed higher ML sway after sensory manipulations disturbing postural control, as a result of which these values approached their perceived LoS more closely than in EF. We conclude that despite a similar fall history, PD patients showed more ML instability than EF, irrespective of sensory manipulation, but had a similar reliance on ankle proprioception. Hence, we recommend that rehabilitation and fall prevention for PD should focus on motor rather than on sensory aspects.